Perception and Health Workers' Attitudes with the Provision of Palliative Care Services for Terminal Patients - Satdiman Tuberta Gulo; Kristian Lase; Tetra Katukrismawati Gulo; Nurhayati Buulolo; Nomy Vera Hutabarat (Sarana Ilmu Indonesia (salnesia), 2026)
Palliative care aims to alleviate the suffering of patients with serious, complex, and terminal illnesses. However, the availability of palliative care services in Indonesia is still limited, and healthcare professionals' understanding is unequal. Although most healthcare professionals demonstrate positive attitudes toward palliative care, gaps in understanding remain that can impact the quality of care provided to terminally ill patients. This study aimed to analyze the relationship between healthcare professionals' perceptions and their attitudes toward providing palliative care to terminally ill patients at Dr. M. Thomsen Regional General Hospital, Nias. The study used a quantitative approach with an observational analytical design and cross-sectional methods. Data were analyzed using a correlation test to determine the relationship between the two variables. The results showed a correlation coefficient (r) of 0.438 with a significance value (p) of 0.001. This indicates a positive and significant relationship between healthcare professionals' perceptions and their attitudes toward providing palliative care. It was concluded that better perceptions are associated with more positive attitudes toward providing palliative care. Therefore, strengthening palliative care education and training is needed to improve healthcare professionals' competence in providing care to terminally ill patients.